2021
DOI: 10.1055/s-0041-1735591
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Coronary Revascularization: Percutaneous Coronary Intervention versus Coronary Artery Bypass Graft Surgery

Abstract: The question of percutaneous coronary intervention (PCI) versus coronary artery bypass graft (CABG) surgery remains among the most important questions in the treatment of coronary artery disease. The leading North American and European societies largely agree on the current guidelines for the revascularization of unprotected left-main disease (ULMD) and multivessel disease (MVD) which are largely supported by the outcomes of several large randomized trials including SYNTAX, PRECOMBAT, NOBLE, and EXCEL. While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…in a number of parameters, including survival. At the same time, meta-analyses by Chew et al and Brown et al revealed the advantage of CABG over PCI in patients with multivessel disease and intermediate and high Syntax scores(25,26), and comparable results for individuals with low SS(26). Our study revealed a predominance in the frequency of MACCE in patients with intermediate SS who underwent PCI compared with those who underwent CABG (81 % and 50 %, re-…”
supporting
confidence: 74%
See 2 more Smart Citations
“…in a number of parameters, including survival. At the same time, meta-analyses by Chew et al and Brown et al revealed the advantage of CABG over PCI in patients with multivessel disease and intermediate and high Syntax scores(25,26), and comparable results for individuals with low SS(26). Our study revealed a predominance in the frequency of MACCE in patients with intermediate SS who underwent PCI compared with those who underwent CABG (81 % and 50 %, re-…”
supporting
confidence: 74%
“…For example, in our study, we retrospectively selected patients who underwent CABG or PCI under actual clinical conditions. Meanwhile, in recent meta-analyses (24)(25)(26)28) comprising RCTs in which the investigators compared the outcomes of PCI and CABG, disparate approaches were implemented to determine study endpoints, and a different composition of SS groups would have affected the authors' recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CABG is associated with more durable revascularization and lower rates of repeat revascularization compared to PCI. However, it is also associated with a longer recovery period and, in some cases, higher rates of early stroke [8,27]. The choice between PCI and CABG is influenced by several factors, including the patient's clinical presentation, the anatomical complexity of CAD, and the presence of comorbid conditions.…”
Section: Current Management Of Coronary Stenosismentioning
confidence: 99%
“…It was found that low- and intermediate-category patients have similar long-term outcomes regardless of the revascularization strategy implemented ( 15 , 16 ). In contrast, CABG yields better outcomes for severe cases than PCI ( 17 ). Nevertheless, the SYNTAX scoring system lacks an individualized approach and clinical variables to guide the choice of the revascularization strategy accurately.…”
Section: Introductionmentioning
confidence: 99%